HUBUNGAN BEBAN KERJA PERAWAT DENGAN RESPONS TIME PERAWAT DI INSTALASI GAWAT DARURAT RSUD BITUNG: RELATIONSHIP OF NURSE WORKLOAD WITH NURSE'S RESPONSE TIME IN EMERGENCY INSTALLATION OF BITUNG Hospital - Sri Wahyuni; Siti Astariyani Latjui (JURNAL FISIOTERAPI DAN ILMU KESEHATAN SISTHANA, 2020)
Workload is the ability of the worker's body to accept the job. From the standpoint of ergonomics, every workload received must be appropriate and balanced against the physical and psychological ability. The good Response time for patients is <5 minutes. Handling of emergency is the whole act performed in emergency conditions that are effectively and efficiently. The purpose of this study was to determine the relationship workload response time nurses with nurses in emergency departments of RSUD Bitung General Hospital. This study was descriptive and cross sectional study. Samples were taken based on the number of respondents as many as 31 nurses by using total sampling. The data collection is done by filling out the observation sheet and questionnaire. Furthermore, the data that has been collected processed with the aid statistics analyzed by chi square test with significance level is ? = 0.05. After the results, the value of p = 0.008, this may imply that there is a relationship between the workload of nurses response time. CONCLUSIONS of this study found that there is a relationship between nurses workload response time. Suggestions for the research was taking place is setting a good system including facilities and infrastructure in order to nurse response time can be improved.